The complete chloroplast genome of a widespread ornamental shrub in China, Magnolia figo (Magnoliaceae) - Zhou, Yuzhen (Mitochondrial DNA B Resour, 2019)
Plants in Michelia, presented by Magnolia figo DC, are wonderful resources in Magnoliaceae, covering a series of aromatic plants. Despite extensive studies in this family, the M. figo complete chloroplast genome and the taxonomical status based on the whole chloroplast sequences remain unclear. Herein, we report the complete chloroplast genome of M. figo. The chloroplast genome was 160,113 bp in length, with a large single-copy (LSC) region of 88,113 bp and a small single-copy (SSC) region of 18,797 bp, separated by two inverted repeat (protein-coding) regions of 26,602 bp. A total of 135 CDSs were found, including 129 genes, 85 protein-coding mRNAs, 36 tRNA genes, and eight rRNA genes. The overall GC content was 39.3%, and GC percentages range from 34.3% to 43.2% throughout LSC, IRs, and SSC regions. Phylogenetic analysis showed that M. figo is most closely to Michelia odora and displayed a relationship that three Michelia were nested inside Magnolia. This announcement of the complete M. figo cp genome sequence could provide valuable information for further breeding, cp genetic modification, and phylogenetic study in Magnoliaceae.